PREPARATION PROGRAM FOR ENHANCING COMMUNICATIVE LANGUAGE TEACHING ABILITY - Saifon Songsiengchai; Punwalai Kewara; Denchai Prabjandee , (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
English language teaching in Thailand has shifted paradigm to implement the Communicative Language Teaching approach and focus on who is expected to understand and be able to create activities for them. Although the English teaching practicum provides an internship for all pre-service teachers, it is found that they lack sophisticated professional knowledge and skills. Pre-service teachers have anxiety about â€œhowâ€ and â€œwhatâ€ to teach, the communicative language teaching activity for supporting students' communication. The Faculty of Education is aimed to train pre-service teachers before teaching in the real context. Preparation programs can prepare pre-service teachers to develop their knowledge and skills of teaching and learn how to competently apply these in the teaching practicum by teacher training. The purpose of this study is to investigate on how to enhance pre-service teachersâ€™ communicative language teaching ability through a designed three-day preparation program for teaching practicum. This qualitative research employed self-reflection to collect the data. Twelve pre-service teachers were selected to participate through purposive sampling. The data were analyzed by using content analysis as the coding technique for grounded theory. The results from the training session phases showed seven topics: confidence, speaking ability awareness, CLT classroom activities, awareness on learnersâ€™ language abilities, error tolerance, accuracy and fluency, and grammar discovery. In conclusion, the designated three-day program enhanced pre-service teachers' CLT regarding their knowledge and awareness of how to apply CLT to their future teaching practicum rather than gaining tangibly improved CLT performance. However, future study, such as on monitoring the pre-service teachers' teaching at the real professional context, i.e., during teaching practicum, is highly suggested to seek empirical evidence of their CLT ability.